TRENDS IN MULTILINGUAL HIGHER EDUCATION IN THE PRE-PANDEMIC DECADE - Natalia Mospan (Borys Grinchenko Kyiv Metropolitan University, 2023)
The pre-pandemic decade (2010-2019) featured the intensive spread of globalisation worldwide, resulting in the spread of multilingual higher education with English-medium instruction. The pre-pandemic decade is likely to have become an era of rapid development of global multilingual higher education. Therefore, the article makes an effort to reveal the trends in developing a global multilingual higher education in the pre-pandemic decade, which could contribute to understanding this phenomenon in the post-pandemic times. Moreover, in the recent publications related to trends in the digital transformation of higher education during the COVID-19 pandemic, the issues of multilingual education are not considered. This remark makes this study timely and significant. The systematic examination of 38 scientific resources published primarily on the Web of Science Core Collection database in 2010-2019 makes it possible to reveal the following trends in multilingual higher education development on macro-, meso-, and micro-levels. The research covers the time frame from 2010 to 2019 - the official beginning of the COVID-19 pandemic. As a result, the following research insights are presented in the paper. First, the author makes an effort to distinguish the main components of English-medium higher education. Second, the article presents the geographical distribution of multilingual higher education (2010-2019). Furthermore, the findings allow the assumption, that multilingual higher education in the pre-pandemic decade (2010-2019) experienced transformation to bilingual type with a dominant English-medium instruction, which, in turn, launched real multilingualism with a tendency to the equal development of national languages in educational settings.